Nation branding: the strategic imperative for sustainable market competitiveness. Issue 2 (15th November 2019) - Hassan, Salah; Mahrous, Abeer A.
Abstract : Purpose: Nation branding strategies are gaining priority as an area of research because of increasing market complexities and the rising importance of national competitiveness ranking. The sustainable development of a nation brand, when properly managed, will provide the economic incentive to attract investors, tourists and generate income for local communities. Therefore, this paper aims to focus on delineating the strategic imperatives for sustainable market competitiveness of nation brands. Design/methodology/approach: The research adopts an eclectic approach in examining a wider range of factors such as sustainability and market competitiveness to develop a synergistic nation brand. Findings: For nation brands to remain competitive, it is essential to understand the key determinants of market competitiveness. These determinants include sustainable tourism factors such as culture, heritage, environmental and integration of internal and external stakeholder groups from the public and private sectors. Originality/value: This paper provides a framework for the analysis of sustainable market competitiveness factors of the nation brand. It also provides implications for nation branding and future research agenda.